Remote ALCAPA Repair—Total Arterial Reconstruction Using Free Aortic Graft Technique. Issue 4 (July 2020) - Peng, Ed; Al-Haideri, Hazim; Dreisbach, John G.
A late presenting anomalous left coronary artery from pulmonary artery (ALCAPA) with remote origin may be associated with several technical caveats due to distance for coronary transfer and inadequate autologous tissues for reconstruction. A technique using full circumferential aortic wall as a free graft that is sutured as a posterior hood on an anterior pulmonary arterial flap is used to achieve reconstruction of a neo-left coronary that is tension free, with laminar flow and without the use of any prosthetic material. The technique with potential modifications described could potentially be applied to any variant of ALCAPA to achieve total arterial reconstruction to yield an optimal long-term outcome.